Anti–α-enolase antibody combined with β2 microglobulin evaluated the incidence of nephritis in systemic lupus erythematosus patients. (March 2019) - Huang, Y; Chen, L; Chen, K; Huang, F; Feng, Y; Xu, Z; Wang, W
Objective: Anti–α-enolase antibody (Ab) combined with β2 microglobulin (β2-MG) were investigated to predict the incidence of nephritis in systemic lupus erythematosus (SLE) patients. Methods: Levels of serum anti–α-enolase Ab and urinary β2-MG were detected in 115 SLE patients, 29 SLE patients with nephritis and 70 healthy controls by ELISA and immunoturbidimetry, respectively. Furthermore, the correlation between anti–α-enolase Ab combined with β2-MG and the incidence of nephritis in SLE patients was evaluated by correlation analysis. Results: The optical density value of serum anti–α-enolase Ab in SLE patients with nephritis (0.84) was greatly increased compared with SLE patients (0.76) or healthy controls (0.54). Moreover, the levels of urinary β2-MG in SLE patients with nephritis (6.75 mg/L) were increased compared with SLE patients (3.45 mg/L) or healthy controls (1.48 mg/L). There was a positive correlation between the level of anti–α-enolase Ab and β2-MG ( r = 0.754). Furthermore, anti–α-enolase Ab combined with β2-MG for evaluating the incidence of nephritis in SLE patients had the best assessment of the effectiveness (area under the receiver operating characteristic curve (AUC): 92.7%) compared with only anti–α-enolase Ab (AUC: 80.9%) or β2-MG (AUC: 84.5%). Conclusion: These data suggested that anti–α-enolase Ab may be a potential indicator for the prediction of nephritis in SLE patients.